Filmes de Zeína e óleos essenciais para revestimento e conservação de Castanha-do-Brasil - Gibelli, Izabel Cristina (2017)
Brazil is a major producer of brazil nuts and the fatty acids present can be oxidized through natural and spontaneous factors causing spoilage of the food and a considerable modification in taste and aroma, characteristically known as rancification. In addition, this product is susceptible to colonization by aflatoxinproducing fungi. In health they can cause intoxications and for the agricultural economy they cause great losses in millions of annual dollars. An alternative is the use of edible coating that acts as a selective barrier against the oxidation determining factors and consequently avoids the production of undesirable flavors and flavors. The objective of this research was to produce coatings composed of zein, corn protein, and essential oils (OE) of clove bud, melaleuca and pink pepper with direct application to the chestnut looking for hydrophobic films. For the characterization of the material was carried out the measurement of contact angle and atomic force microscopy (MFA). The acceptance of the coated nuts was evaluated through sensorial analysis. After thermal acceleration in the oven at 50 ° C for 14, 21 and 28 days the oil was extracted and characterized by gas chromatography (GC) and lipid oxidation by nuclear magnetic resonance (¹H NMR). The antifungal action of essential oils in 0.5, 1 and 1.5% concentrations was also evaluated. The results for the contact angle measurement and the MFA images were consistent, showing that the water absorption capacity decreases with the increase of the clove oil concentration, that is, the film containing clove oil is more hydrophobic with concentrations Higher OE, on the other hand, the film containing OE of melaleuca is more hydrophobic at lower concentrations. The sensorial analysis showed that the nuts coated with the material were well accepted by the evaluators. GC showed variations of fatty acids proving oxidative action. Integrations of the NMR peaks showed that the coating containing pink pepper and melaleuca were effective in retarding the oxidation process. As for the antifungal action the clove oil has a fungicide action and the oil of pink pepper and melaleuca has fungistatic action for Aspergillus flavus.